2010
DOI: 10.1242/jcs.063636
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric function of mammalian telomerases at short telomeres

Abstract: SummaryTelomerase synthesizes telomeric sequences and is minimally composed of a reverse transcriptase (RT) known as TERT and an RNA known as TR. We reconstituted heterologous mouse (m) and human (h) TERT-TR complexes and chimeric mTERT-hTERT-hTR complexes in vitro and in immortalized human alternative lengthening of telomere (ALT) cells. Our data suggest that species-specific determinants of activity, processivity and telomere function map not only to the TR but also to the TERT component. The presence of hTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 69 publications
(138 reference statements)
1
23
0
Order By: Relevance
“…It is also plausible that telomerase activity could promote efficient repair following complete telomere loop excision in ALT cells, leading to a gain in efficiency of progression through specific phases of the cell cycle. Indeed, ALT-dependent homologous recombination resulted in heterogeneous telomeres within the cell population, and it has been previously shown that forced expression of human telomerase activity can limit the number of telomere DNA repeat signal-free ends in ALT cells (Fakhoury et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is also plausible that telomerase activity could promote efficient repair following complete telomere loop excision in ALT cells, leading to a gain in efficiency of progression through specific phases of the cell cycle. Indeed, ALT-dependent homologous recombination resulted in heterogeneous telomeres within the cell population, and it has been previously shown that forced expression of human telomerase activity can limit the number of telomere DNA repeat signal-free ends in ALT cells (Fakhoury et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The high tolerance of hTERT towards TR of different species was previously demonstrated using in vitro assays as well as in cellular systems [22,24,25,27]. We further investigated if vTR would be able to reconstitute telomerase activity in a cellular context (Fig.…”
Section: In Human Cells Vtr Is Not Able To Reconstitute a Functionalmentioning
confidence: 86%
“…Competitive RNA binding assays were performed according to previously described protocols [25]. The viral and human TRs were in vitro transcribed in the presence or absence of  32 P UTP.…”
Section: In Vitro Rna Binding Assaymentioning
confidence: 99%
See 2 more Smart Citations